Clinical characteristics of Thai patients with psoriasis - Sukhum Jiamton (2018)
Objective: To reveal the clinical manifestations, aggravating factors, factor associated with severity, and treatment of psoriasis in Thai patients. Material and Method: The data of psoriasis patients who had been visited Dermatologic outpatient clinic, Siriraj Hospital between July 2002 and July 2008 were retrospectively reviewed. Results: One thousand eighty two patients were studied. The male to female ratio was 1.2:1 and the peak age of onset was in the 40 to 49 year-old age group. The most common aggravating factor was stress (50%), followed by trauma (39%) and weather condition (35%). The majority of patients had plaque type (72.8%). Male gender, smoking, alcohol intake, and nail abnormalities were related to severe psoriasis (PASI > 10). Conclusion: The present study demonstrated the demographic data of Thai psoriasis patients in a large number of population. These data would be beneficial for national public health development of Thailand in order to provide the better care for Thai psoriasis patients.